HIV/AIDS in South Africa: an overview - Gilbert Leah; Walker Liz (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2002)
This paper presents an overview of the development of HIV/AIDS in South Africa, taking into consideration the social context and analyzing the factors most likely to have influenced its spread as well as the societal response to it. The authors argue that macro factors such as social and political structures, in addition to behavioral ones, have combined to shape the course of the epidemic. Since various factors linked to social inequalities have combined to shape the pattern and growth of the HIV/AIDS epidemic in South Africa, it is inappropriate to focus on only one dimension in an attempt to combat the epidemic. Following the psycho-socio- environmental model, all potential contributing elements need to be addressed simultaneously. This calls for a true interdisciplinary and multi-sectorial approach. It also requires great commitment as well as strong political will.